Single leg hopping in children with fetal alcohol spectrum disorder: Dynamic postural stability and kinematics. Issue 4 (October 2020) - Moore, Keryn; Cockcroft, John; Louw, Quinette; Brink, Yolandi
Abstract: Background: This study compared dynamic postural stability (DPS) and lower limb kinematics during single leg hopping (SLH) performed by typically-developed children from urban and rural settings and children with Fetal Alcohol Spectrum Disorder (FASD) from a rural setting. Methods: Typically-developed nine-year-old children from an urban (n = 27) and rural setting (n = 14) (controls), and nine-year-old children with FASD from a rural setting (n = 14) (cases) performed SLH and landing on a pressure mat. Motion analysis systems described 1) Spatiotemporal and centre of pressure parameters (COP) and lower limb sagittal plane kinematics. Descriptive results are presented in median and ranges and differences between groups were determined by Kruskal-Wallis and Mann-Whitney U statistical tests. The level of significance was p < 0.05. Results: During hopping, the urban controls had longer stance and swing times (p < 0.001) than the rural groups. The urban controls remained in greater hip flexion compared to the case group (p = 0.02). The urban controls landed in more plantarflexion at initial foot contact (IFC) than the cases (p < 0.001) and the rural controls (p = 0.03). The rural groups landed with greater knee extension at IFC than the urban controls (cases p = 0.04; rural controls p < 0.001). During the landing motion, the urban controls moved into more hip flexion compared to the cases (p = 0.015) and the rural controls (p = 0.026). The cases displayed greater COP anteroposterior values during landing compared to both control groups, but the case group displayed the fastest time to stability. Conclusion: The different hopping strategies observed provides an indication of the movement capabilities of these groups.